Managerial skill acquisition and the theory of economic development - Beaudry, Paul 1960-; Francois, Patrick 1965- (National Bureau of Economic Research, 2005)
"Micro level studies in developing countries suggest managerial skills play a key role in the adoption of modern technologies. The human resources literature suggests that managerial skills are difficult to codify and learn formally, but instead tend to be learned on the job. In this paper we present a model of the interactive process between on-the-job managerial skill acquisition and the adoption of modern technology. The environment considered is one where all learning possibilities are internalized in the market, and where managers are complementary inputs to non-managerial workers. The paper illustrates why some countries may adopt modern technologies while others stay backwards. The paper also explains why managers may not want to migrate from rich countries to poor countries as would be needed to generate income convergence"--National Bureau of Economic Research web site.
Keywords: Entwicklungsländer; Industrial management -- Developing countries; Technology -- Developing countries